2016
DOI: 10.3847/2041-8205/824/1/l8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Formation of the Gw150914 Binary Black Hole

Abstract: We explore the possibility that GW150914, the binary black hole (BBH) merger recently detected by Advanced LIGO, was formed by gravitational interactions in the core of a dense star cluster. Using models of globular clusters (GCs) with detailed N-body dynamics and stellar evolution, we show that a typical cluster with a mass ofis optimal for forming GW150914-like BBHs that will merge in the local universe. We identify the most likely dynamical processes for forming GW150914 in such a cluster, and we show that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
176
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(185 citation statements)
references
References 42 publications
8
176
1
Order By: Relevance
“…As was done in Rodriguez et al (2016), we assume that the GC population of the local universe is comprised of ∼ 44% high-metallicity GCs (0.25Z ), and ∼ 56% low-metallicity GCs (0.05Z and 0.01Z ). We further assign to each GC a tidal radius based on its galactocentric distance, which we assume to be correlated to its stellar metallicity based on observations of the Milky Way and other galaxies (Harris 2010).…”
Section: Galactic Field and Globular Cluster Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…As was done in Rodriguez et al (2016), we assume that the GC population of the local universe is comprised of ∼ 44% high-metallicity GCs (0.25Z ), and ∼ 56% low-metallicity GCs (0.05Z and 0.01Z ). We further assign to each GC a tidal radius based on its galactocentric distance, which we assume to be correlated to its stellar metallicity based on observations of the Milky Way and other galaxies (Harris 2010).…”
Section: Galactic Field and Globular Cluster Modelsmentioning
confidence: 99%
“…The integral of the GC mass function over that bin then determines the weight assigned to that model. In other words, GC models with larger masses (3 × 10 5 M to 6 × 10 5 M , corresponding to models with initial particle numbers of 1 × 10 6 and 2 × 10 6 ) contribute more binaries than clusters with smaller masses (see Rodriguez et al 2016, for details). Once we select this population of binaries from all clusters, we generate a five-dimensional Gaussian kernel density estimate (KDE) from the formation masses, separation, eccentricity and ejection times of the BBH population.…”
Section: Galactic Field and Globular Cluster Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another reason to expect high values of q is scattering processes, either involving the BBH and an additional single BH, or between two BBHs. Simulations have shown that in dense environments, binaries tend to exchange components, preferentially ejecting their smaller partners in favor of more massive companions [72][73][74].…”
Section: The Mass Ratio In Bbhs and The 2d Bhmfmentioning
confidence: 99%